Strategic Development of a Commercial Bank in Modern Conditions ("Journal "U". Economy. Management. Finance.", 2017)
Planning and implementation of a commercial bank's strategy is a complex of interconnected systems and subsystems which allow an organization to develop and reach the maximum synergy effect. The strategic plan is a possibility for the bank to increase considerably its competitiveness and stability. Creation of the system of the strategic planning in the bank is a passing of certain stages, each of which is directed to achievement of specific quantitative indices.
Keywords: strategic development; strategic planning; bank; banking sector; development strategy of bank; elaboration of strategy